INTEGRATED MARKETING STRATEGIES IN BOOSTING THE CUSTOMER EXPERIENCE: AN APPROACH TO THE SERVICES INDUSTRY - H. Mohdari; Pamungkur; Mariatul (Adisam Publisher, 2024)
This article aims to explore the influence of Integrated Marketing Strategy (IMS) in improving customer experience in the context of the financial services industry. It involves a review of the literature on integrated marketing strategies and customer experience, in the financial service industry context, which can lead to an in-depth understanding of the impact of IMS on enhancing customer experience. IMS helps deliver brand messages consistently across different channels, encourages higher customer engagement, and creates more personal and relevant interactions with customers. Moreover, in the context of financial services, IMS can also help build customer confidence, which is critical in this industry. However, the study also emphasizes that the success of IMS in improving customer experience requires a deep understanding of customers and technology investments to analyze customer data.